ANALISIS PENTINGNYA INTERAKSI KELAS DALAM PENGAJARAN KETERAMPILAN BERBICARA DI KELAS DUA SMA 6 BENGKULU: Analysis The Importance of Calssroom Interaction in Teaching Speaking Skill at Second Grade SMA 6 Bengkulu - Gandari, Meisy; Nurcholis, Ivan Achmad (PUAN INDONESIA, 2024)
Abstract: This research is entitled "The Importance of Classroom Interaction in Teaching Speaking skills at Second Grade SMA 6 Bengkulu" The purpose of this research is to analyze how the importance of classroom interaction in teaching speaking skills in class. The method used in this research is using qualitative method, by using direct observation method to students and teachers in the learning process. The subjects in this research are an English teacher and second grade students of SMAN 6 Bengkulu. The result of this research is, class interaction is very important in learning speaking in class especially in learning English. Because through class interaction, we can find out the ability of students and how to develop and foster students' confidence to speak and interact during the learning process. In this context, the teacher has an important role in supporting classroom interaction because the teacher is a motivator as well as a facilitator to develop students' abilities. When learning English, it is found that there are still many students who are not confident and choose to be silent, and there are also those who speak but still use the mother tongue as a whole word with the excuse of not knowing and afraid of being wrong, therefore it is advisable for teachers to provide encouragement, motivation and praise that builds students' confidence to speak, especially using English.